1989
DOI: 10.1083/jcb.108.5.1589
|View full text |Cite
|
Sign up to set email alerts
|

Binding of an N-ethylmaleimide-sensitive fusion protein to Golgi membranes requires both a soluble protein(s) and an integral membrane receptor.

Abstract: Abstract. An N-ethylmaleimide (NEM)-sensitive fusion protein (NSF) has recently been purified on the basis of its ability to restore transport to NEM-inactivated Golgi membranes in a cell-free transport system. NSF is a peripheral membrane protein required for the fusion of transport vesicles. We now report the existence of two novel components that together bind NSF to Golgi membranes in a saturable manner. These components were detected by examining the requirements for reassociation of purified NSF with Gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(85 citation statements)
references
References 19 publications
2
81
0
2
Order By: Relevance
“…Most α helices of α-SNAP are clearly visible in the map except for the very C-terminal end, near which there are weak densities possibly corresponding to the N-domain of NSF known to interact with α-SNAP's C terminus [19][20][21][22][23]. The four-helical bundle of the SNARE complex fits perfectly in the central left-handed four threadlike densities albeit with the side chain of each residue in the helix unsolved.…”
Section: S Particle Segmentation and 3d Reconstruction Of The α-Snamentioning
confidence: 73%
See 2 more Smart Citations
“…Most α helices of α-SNAP are clearly visible in the map except for the very C-terminal end, near which there are weak densities possibly corresponding to the N-domain of NSF known to interact with α-SNAP's C terminus [19][20][21][22][23]. The four-helical bundle of the SNARE complex fits perfectly in the central left-handed four threadlike densities albeit with the side chain of each residue in the helix unsolved.…”
Section: S Particle Segmentation and 3d Reconstruction Of The α-Snamentioning
confidence: 73%
“…We also showed that the N-domains of NSFs move to the periphery of the complex when ATP is hydrolyzed to ADP. As the C-terminal domain of α-SNAP interacts directly with the N-domain of NSF [19][20][21][22][23], the movement of the N-domain in the 20S particle very likely causes the similar movement of α-SNAP. It is therefore plausible that, within an assembled 20S particle, a conformational change of the NSF triggered by ATP hydrolysis would be transduced to the tetrameric α-SNAP for it to unwind the SNARE complex (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a 115 kDa peripheral membrane protein (Waters et al, 1992), an N-ethylmaleimide sensitive fusion protein (NSF; Block et al, 1988) and soluble NSF-attachment proteins, (SNAPS; Clary et al, 1990) which recruit NSF to specific receptors on Golgi membranes (Weidman et al, 1989). Recent studies have established that short peptides derived from the N-terminus of ARFs block the intra-Golgi transport assay .…”
Section: Introductionmentioning
confidence: 99%
“…Il paraissait vraisemblable que les SNARE seraient insérées directement dans les membranes parce que les récepteurs de SNAP gardent la capacité de lier SNAP, même après extraction des membranesà l'aide d'un traitement alcalin fort, dont la brutalité enlève tout ce qui n'est pas protéines membranaires intégrales (Weidman et al, 1989). La purification des protéines de membrane devint notre priorité absolue, car nous supposions que la fusion des bicouches lipidiques nécessiterait des protéines ancréesà la membrane.…”
Section: La Découverte Du Complexe Snareunclassified